2008
DOI: 10.1016/j.neuroimage.2008.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable roles of medial orbitofrontal cortex in human operant extinction learning

Abstract: Operant extinction, which features modification of instrumental responses to stimuli following a change in associated reinforcement, is an important form of learning for organisms in dynamic environments. Animal studies have highlighted orbital and medial prefrontal cortex and amygdala as mediators of operant extinction. Yet little is known about the neural mediators of operant extinction learning in humans. Using a novel fMRI paradigm, we report dissociable functional responses in distinct regions of medial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…The first is that in older individuals, vlPFC engages vmPFC, which in turn exerts a modulatory influence on the amygdala. This possibility is appealing given vmPFC's role in regulatory processes including fear extinction and reversal learning (Milad et al 2007;Finger et al 2008;Schiller et al 2008;Sehlmeyer et al 2009;Schiller and Delgado 2010), yet the fact that vlPFC recruitment and vmPFC-amygdala connectivity were uncorrelated makes it seem less plausible. The second possibility is that increasingly negative vmPFC-amygdala coupling indexes the degree to which the amygdala is receptive to prefrontal modulation across development (Gee et al 2013), but that vlPFC and vmPFC exert independent influences on the amygdala during reappraisal.…”
Section: A Model Of Negative Emotion Regulation In the Developing Brainmentioning
confidence: 99%
“…The first is that in older individuals, vlPFC engages vmPFC, which in turn exerts a modulatory influence on the amygdala. This possibility is appealing given vmPFC's role in regulatory processes including fear extinction and reversal learning (Milad et al 2007;Finger et al 2008;Schiller et al 2008;Sehlmeyer et al 2009;Schiller and Delgado 2010), yet the fact that vlPFC recruitment and vmPFC-amygdala connectivity were uncorrelated makes it seem less plausible. The second possibility is that increasingly negative vmPFC-amygdala coupling indexes the degree to which the amygdala is receptive to prefrontal modulation across development (Gee et al 2013), but that vlPFC and vmPFC exert independent influences on the amygdala during reappraisal.…”
Section: A Model Of Negative Emotion Regulation In the Developing Brainmentioning
confidence: 99%
“…Instrumental conditioning is based on two different processes computed in distinct brain areas, i.e., goal-directed learning of associations between responses and outcomes and habit learning of associations between stimuli and responses. Devaluation of outcomes in instrumental conditioning showed that the medial OFC is critical involved in the first process, associating a response with its incentive value of the outcome (Valentin et al 2007;Finger et al 2008).…”
Section: The Medial Ofc In Instrumental Conditioningmentioning
confidence: 99%
“…In appetitive Pavlovian extinction, NA efflux in mPFC of rats was increased (Mingote et al, 2004). During successful operant extinction learning, activity in frontopolar OFC in humans increased while activity in mOFC decreased (Finger et al, 2008), compared to acquisition of the stimulus-reinforcement association. Hippocampal neurons respond to a conditioned stimulus whether it signals food or a shock, thus they are involved in both aversive and appetitive conditioning (Segal et al, 1972).…”
Section: Introductionmentioning
confidence: 97%